Knowledge landscape of open access in academic libraries through bibliometric analysis 2020-2025 - Bestari, Melati Purba; Yuadi, Imam; Albigaeri, Syahruly Nizar (Jurnal Kajian Informasi & Perpustakaan, 2025)
Background: The digital era transformation has changed the role of academic libraries, which initially served as repositories for physical collections and have evolved into facilitators of digital information access and initiators of change in open-access management. The COVID-19 pandemic accelerated the adoption of open access due to the urgent need for unrestricted access to scientific information. Purpose: This study aimed to map the knowledge landscape of open access in academic libraries through a comprehensive bibliometric approach for 2020-2025, identifying dominant themes, intellectual structures, collaboration patterns, and emerging trends. Methods: Data were collected from the Scopus database using the TITLE-ABS-KEY search strategy ("open access" AND "academic library"). Analysis was conducted using Bibliometrix in R Statistical Software version 4.3.0 and Biblioshiny, covering Conceptual Structure Analysis, Multiple Correspondence Analysis, Intellectual Structure Analysis, Social Structure Analysis, and Thematic Evolution Analysis. Results: The analysis showed that 118 documents from 57 publication sources were dominated by collaborative research (72.1%), with limited international collaboration (6.78%). Publication productivity peaked in 2020 (26 articles) and then declined continuously. The United States dominated with 114 citations, followed by Pakistan (36) and South Africa (33). Institutional repositories, digital libraries, and scholarly communication have emerged as central themes connecting various aspects of research. Conclusion: The open-access knowledge landscape has evolved from a focus on technical infrastructure to a strategic, holistic approach. Implications: This research provides practical guidance for librarians and policymakers to develop more effective strategies in the digital transformation era.